Poetics of the urban, poetics of the self: a comparative study of selected works by Jorge Luis Borges and Jacques Réda - Puello Alfonso, SL (2014)
This thesis explores the poetic representation of Buenos Aires and Paris in selected works by Jorge Luis Borges and Jacques Réda respectively. Its primary aim is to analyse the relational phenomenon between the construction of these poets' personal maps of the city and the concomitant formation of the poetic self. The principal point of departure is Jacques Réda's Ferveur de Borges (1987), a collection of essays and poems published individually between 1957 and 1986, where the author expresses his admiration for Borges, shows his broad and critical knowledge of Borges's works and establishes the similarities between their poetics of the urban and poetics of the self. Another important aim of this thesis is therefore to ascertain the extent of Borges's influential role in Réda's poetics, but also how reading Borges through Réda enhances our understanding of Borges's urban poetry. This comparison reveals that Borges and Réda gravitate towards places within the city, but mostly its periphery, characterised by their unpretentious, soulful and heterotopic qualities — places where the poets feel a sense of belonging. Their objective is to restore, through the prism of their minds and their physical investment in space, the provincial spirit of Buenos Aires and Paris, hidden behind the dynamism of the modern metropolises they have become. As a consequence of this communion between self and place they explore the possibility of being on the brink of a revelatory experience that speaks to the enigma of life. The wider scope of the thesis addresses the historical and cultural relationship between Buenos Aires and Paris, Borges's and Réda's redefinition of the centre/periphery dichotomy, the evening as a temporal locale and the distinction between poetic destiny and aesthetic experience.